Population structure and genetic relationships between Ethiopian and Brazilian Coffea arabica genotypes revealed by SSR markers - da Silva, Bruna Silvestre Rodrigues; Sant’Ana, Gustavo César; Chaves, Camila Lucas; Godoy Androcioli, Leonardo; Ferreira, Rafaelle Vecchia; Sera, Gustavo Hiroshi; Charmetant, Pierre; Leroy, Thierry; Pot, David; Domingues, Douglas Silva [UNESP]; Pereira, Luiz Filipe Protasio (Springer Nature, 2019)
Information about population structure and genetic relationships within and among wild and brazilian Coffea arabica L. genotypes is highly relevant to optimize the use of genetic resources for breeding purposes. In this study, we evaluated genetic diversity, clustering analysis based on Jaccard’s coefficient and population structure in 33 genotypes of C. arabica and of three diploid Coffea species (C. canephora, C. eugenioides and C. racemosa) using 30 SSR markers. A total of 206 alleles were identified, with a mean of 6.9 over all loci. The set of SSR markers was able to discriminate all genotypes and revealed that Ethiopian accessions presented higher genetic diversity than commercial varieties. Population structure analysis indicated two genetic groups, one corresponding to Ethiopian accessions and another corresponding predominantly to commercial cultivars. Thirty-four private alleles were detected in the group of accessions collected from West side of Great Rift Valley. We observed a lower average genetic distance of the C. arabica genotypes in relation to C. eugenioides than C. canephora. Interestingly, commercial cultivars were genetically closer to C. eugenioides than C. canephora and C. racemosa. The great allelic richness observed in Ethiopian Arabica coffee, especially in Western group showed that these accessions can be potential source of new alleles to be explored by coffee breeding programs.
Keywords: Coffea spp; Cultivated and wild gene pools; Genetic diversity; Population structure and relationships; SSR markers